2014
DOI: 10.1364/ao.53.004768
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index measurement of turbid media by transmission of backscattered light near the critical angle

Abstract: We investigate experimentally the determination of the effective refractive index (RI) of a turbid particle suspension from the angle dependence of light scattered by the particles and then transmitted into a transparent prism of higher RI. We assembled a versatile experimental device that may be recognized as an Abbe-type refractometer in which the sample is illuminated from the prism side and use it to measure the intensity profile of diffuse light refracted into the prism around the critical angle. By fitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
(51 reference statements)
1
23
1
Order By: Relevance
“…This result seems to contradict a recent interesting experiment [34] where it is shown that α becomes increasingly insensitive to variations in particle concentration at extremely high particle concentrations, whereas n r remains sensitive. We point out that there is no such contradiction.…”
Section: B Onset Of Aggregation Due To Changes In Ph or Ionic Strengcontrasting
confidence: 86%
“…This result seems to contradict a recent interesting experiment [34] where it is shown that α becomes increasingly insensitive to variations in particle concentration at extremely high particle concentrations, whereas n r remains sensitive. We point out that there is no such contradiction.…”
Section: B Onset Of Aggregation Due To Changes In Ph or Ionic Strengcontrasting
confidence: 86%
“…[49][50][51] In addition to OCT, the Abbe prism classical refractometry is an attractive tool for assessment of phase transitions in in vitro studies. 52,53 For comparison of RI measurements performed by OCT and Abbe refractometry, it should be considered that due to a broadband light source used in OCT it measures the group RI of a material, as a single wavelength measurements of Abbe refractometry give the phase RI. The group and phase RI are related; however, in dispersive media they are different.…”
Section: Optical Coherence Tomography and Abbe Refractometrymentioning
confidence: 99%
“…where q is the molecular charge, N is the number of molecules per unit volume, m is the molecular mass, ω is the probing light frequency, ω 0 is the central frequency of molecular absorption band, and γ is the attenuation coefficient. [21][22][23][24][25] Over the last decades, various techniques to determine RI of biological tissues were developed; they include confocal microscopy, 1,6 optical fiber cladding method, 27 minimum deviation angle method, 28,29 optical coherent tomography with multiple modifications, 6,9,[30][31][32][33][34][35][36] total internal reflection method, 26,37,38 measurement of the intensity profile of diffuse light refracted into the prism around the critical angle, 39 various modifications of nonlinear phase microscopy, [40][41][42] and quantitative phase imaging techniques. 12,43,44 Because of the strong hemoglobin absorption, direct measurements of the real part of RI using conventional refractometers (for example, an Abbe refractometer) have proven to be difficult, and data are available at a few wavelengths only.…”
Section: Introductionmentioning
confidence: 99%